2008
DOI: 10.1080/02640410802027378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 72-h of exercise abstinence on affect and body dissatisfaction in healthy female regular exercisers

Abstract: In this study, we compared the effects of a 72-h exercise abstinence period and normal exercise on the affect and body dissatisfaction of 58 healthy women (mean age 26.1 years, s = 8.2) who exercised at least four times per week, and explored the relationship between the changes in affect and body dissatisfaction. Participants completed the UWIST-MACL and Body Dissatisfaction Scale to assess affect and body image, and were randomized to an abstinence or control group. Affect and body image for both groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As suggested by a study carried out in female rats, the loss of sensitivity to opioids under exercise conditions may actually be fully reversed when the animals do not have access to RWs anymore (Smith and Lyle, 2006). This potential anhedonic-like behaviour induced by a brief period of exercise deprivation (observed in our WT animals) has also been reported by healthy women (who exercise at least four times per week) during a 72 h exercise abstinence (Niven et al, 2008).…”
Section: Discussionmentioning
confidence: 56%
“…As suggested by a study carried out in female rats, the loss of sensitivity to opioids under exercise conditions may actually be fully reversed when the animals do not have access to RWs anymore (Smith and Lyle, 2006). This potential anhedonic-like behaviour induced by a brief period of exercise deprivation (observed in our WT animals) has also been reported by healthy women (who exercise at least four times per week) during a 72 h exercise abstinence (Niven et al, 2008).…”
Section: Discussionmentioning
confidence: 56%
“…While a significant number of studies (n = 11) investigated these negative effects as potential withdrawal symptoms within an addiction framework, the remainder did not. Notable theoretical perspectives included interpreting these effects in light of potential biological determinants (e.g., Antunes et al, 2016;Glass et al, 2004;Kop et al, 2008;Poole et al, 2011;Weinstein et al, 2007;Zeller et al, 2011), or as negative non-addiction-related health outcomes resulting from not exercising (Ablin et al, 2013;Berlin et al, 2006;Niven et al, 2008). Across all behaviors examined in the present review, only negative abstinence effects from exercise have been interpreted from a biological perspective.…”
Section: Sr(all)mentioning
confidence: 99%
“…In a study of longer‐term impacts, Guszkowska and Sionek () showed a significant stable change in mood profile as a result of a 12‐week‐long aerobic training program. Niven, Rendell, and Chisholm () showed that a 72‐hr exercise abstinence period resulted in mood deterioration and body dissatisfaction in regularly active women.…”
Section: Introductionmentioning
confidence: 99%